Gambaran Penyesuaian diri Lansia dalam Konteks Model Adaptasi Roy di Loka Rehabilitasi Sosial Lanjut Usia Kendari - Anggi Nurza’da Pebrianti M; Diah Indriastuti; Mien Mien (Holistic Nursing and Health Science, 2020)
Introduction: Changes in the elderly need social support from friends, family and the surrounding environment so that they can easily adjust to the changes that occur. This study aimed to describe the self-adjustment of the elderly in the context of Roy's Adaptation Model at the Elderly Social Rehabilitation (ESR) of Kendari.Methods:  The study was a qualitative research with a phenomenology approach. The participants in this study were eight elderly who lived in Kendari's ESR and two nurses as triangualition participants. Sampling used a purposive sampling technique. The researchers employing in-depth interview, observation, dan documentation study in collecting data. The data were analyzed using thematic analysis.Results: The study resulted in four themes including entry process to ESR, self-change, coping mechanisms and response indicate that the elderly self-adjusment social rehabilitationsite in the context of Roy’s Adaptation Model describing the human adaptation system through several stages, namely input, control and output where in the life of the elderly who live in ESR is influenced by the entry process in LRSLU as an internal stimulus or an external stimulus. Thus, there is a process of self-adjustment in the form of self-change and coping mechanisms, with various kinds of coping carried out to produce a behavior in the form of adaptive or maladaptive responses.Conclusion: This study concludes that the elderly in adjusting themselves through several stages namely input, control and output to adapt to the environment goodbye in the elderly social rehabilitation workshop (ESR) Kendari with self-changes and various coping mechanisms so as to produce behavioral responses.